ESTIMASI PARAMETER SERVOMOTOR DC MENGGUNAKAN PROSES OPTIMASI - Arjoni Amir (Jurnal Perangkat Nuklir, 2010)
A PARAMETER ESTIMA TION FOR DC SERVOMOTOR BY USING OPTIMIZA TION PROCESS. Modeling and simulation parameters of DC servomotor using Mat/ab Simulink software have been done. The objective to define the DC servomotor parameter estimation is to get DC servomotor parameter values (B, La, Ra, Km, J) which are significant value that can be used for actuation process of control systems. In the analysis of control systems DC the servomotor expressed by transfer function equation to make faster to be analyzed as a component of the actuator. To obtain the data model parameters and initial conditions of the DC servomotors is then carried out the processof modeling and simulation in which the DC servomotor combined with other components. To obtain preliminary data of the DC servomotor parameters as estimated veiue, it is obtained from the data factory of the DC servomotor. The initial data parameters of the DC servomotor are applied for the optimization process by using nonlinear least square algorithm and minimize the cost function value so that the DC servomotors parameter values are obtained significantly. The result of the optimization process of the DC servomotor parameter values are B = 0.039881, J = 1.2608e-007, Km = 0.069648, La = 2. 3242e-006 and Ra = 1.8837. ESTIMASI PARAMETER SERVOMOTOR DC MENGGUNAKAN PROSES OPTIMASI. Telah dilakukan pemodelan dan simulasi parameter servomotor DC dengan menggunakan proses optimasi dengan perangkat lunak Simulink Matlab. Tujuan estimasi parameter servomotor DC ada/ah untuk mendapatkan nilai parameter servomotor DC (B, La, Ra, Km, J) yang signifikan sehingga nilai parameter ini bisa dipakai dalam rangkaian sistem pengendalian yang berfungsi sebagai aktuator. Dalam analisis sistem pengendalian servomotor DC dinyatakan dalam persamaan fungsi transfer sehingga mudah dianalisis sebagai komponen aktuator. Untuk mendapatkan model data parameter dan kondisi awal servomotor DC tersebut maka dilakukan proses pemodelan dan simulasi dimana servomotor DC digabung dengan komponen lain. Untuk mendapatkan data awal parameter servomotor DC bisa diperoleh dari nilai estimasi semen tara pabrik servomotor DC tersebut. Data awal parameter servomotor DC tersebut kemudian dilakukan proses optimasi menggunakan algoritma nonlinear least square dan mengecilkan nilai cost function sehingga diperoleh nilai parameter servomotor DC yang signifikan. Hasil proses optimasi diperoleh nilai parameter servomotor DC yaitu dengan B = 0.039881, J = 1.2608e-007, Km = 0.069648, La = 2. 3242e-006 dan Ra =1.8837